The author's voice in classical and late antiquity - Marmodoro, Anna, 1975-; Hill, Jonathan, 1976- (Oxford University Press, 2013)
This volume focuses on the authorial voice in antiquity exploring the different ways in which authors presented and projected various personas. In particular, it questions authority and ascription in relation to the authorial voice, and considers how later readers and authors may have understood the authority of a text's author.